2016
DOI: 10.14569/ijacsa.2016.070454
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Context Modelling in Pervasive Context-Aware Computing Environment: A Logic Perspective

Abstract: Abstract-Pervasive context-aware computing, is one of the topics that received particular attention from researchers. The context, itself is an important notion explored in many works discussing its: acquisition, definition, modelling, reasoning and more. Given the permanent evolution of context-aware systems, context modeling is still a complex task, due to the lack of an adequate, dynamic, formal and relevant context representation. This paper discusses various context modeling approaches and previous logic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Spatiotemporal extent is used in many applications for smart environment. As in [15], authors proposed a preliminary formal spatiotemporal context modeling based on first order logic. In the system, simple context is described by logic model then complicated context is represented using Boolean operator to generate high level context.…”
Section: Related Workmentioning
confidence: 99%
“…Spatiotemporal extent is used in many applications for smart environment. As in [15], authors proposed a preliminary formal spatiotemporal context modeling based on first order logic. In the system, simple context is described by logic model then complicated context is represented using Boolean operator to generate high level context.…”
Section: Related Workmentioning
confidence: 99%
“…According to Mohan and Singh in [21], formal semantics of ORM and Context Modeling Language (CML) can be supplemented to provide integration with other implementations. Graphical modeling technique as its strength provides relationship modeling, flexible implementation and it is very useful for data storage and historic context store [23]. However, the limitations of graphical modelling technique include its complexity to retrieve information which requires obligatory configuration.…”
Section: Figure 4 Sample Entity Relations Graphical Modelmentioning
confidence: 99%
“…Perera et al in [36] surveyed high-level context modelling techniques and concluded that diversification of modelling techniques is the best way to provide efficient results which will lessen each other's weaknesses. Finally, [23] discussed the context modelling techniques and used logic based technique to model spatiotemporal context. They finally concluded that no modelling technique is ideal to be used in a standalone manner.…”
Section: Best Choice Techniquementioning
confidence: 99%